2020
DOI: 10.1194/jlr.p119000543
|View full text |Cite
|
Sign up to set email alerts
|

LDL subclass lipidomics in atherogenic dyslipidemia: effect of statin therapy on bioactive lipids and dense LDL

Abstract: Atherogenic LDL particles are physicochemically and metabolically heterogeneous. Can bioactive lipid cargo differentiate LDL subclasses, and thus potential atherogenicity? What is the effect of statin treatment? Obese hypertriglyceridemic hypercholesterolemic males [n = 12; lipoprotein (a) <10 mg/dl] received pitavastatin calcium (4 mg/day) for 180 days in a single-phase unblinded study. The lipidomic profiles (23 lipid classes) of five LDL subclasses fractionated from baseline and post-statin plasmas were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 79 publications
3
60
0
Order By: Relevance
“…SdLDLs have a prolonged residence time in the circulation with extensive inter-particle transfer via the cholesteryl ester transfer protein (CETP), increasing risk of plaque formation. Furthermore, the low affinity of sdLDL for the LDL receptors in the liver is also leading to a lower reuptake and longer residence in the circulation [ 22 ]. In the present study, we showed an early percent reduction of sdLDL after 7 days of fasting and still more after 14 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SdLDLs have a prolonged residence time in the circulation with extensive inter-particle transfer via the cholesteryl ester transfer protein (CETP), increasing risk of plaque formation. Furthermore, the low affinity of sdLDL for the LDL receptors in the liver is also leading to a lower reuptake and longer residence in the circulation [ 22 ]. In the present study, we showed an early percent reduction of sdLDL after 7 days of fasting and still more after 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…The former pathway typically predominates [ 21 ]. LDL are a continuum of particles distributed over densities ranging from 1.019 to 1.063 g/ml, further sub-classified into large buoyant LDL1, intermediate LDL2 and small dense LDL3 (sdLDL) [ 22 ]. The sdLDL particles are characterized by a low lipid/protein ratio and small particle size, both favouring an enhanced transcytosis across the arterial endothelium triggering atheroma formation [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple linear regressions were run to assess associations between lipids, age, sex and the interaction between age and sex, while adjusting for the following previously described clinical confounders: body fat (%), statins intake, HbA1c (%), daily total physical activity (min), blood sampling time and fasting time prior to blood sampling [ 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. Lipids were used as dependent variables, while the other parameters served as independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Statin therapy showed conflicting results on ceramide levels. A recent study reported no reduction in absolute ceramide content within LDL particles, or even an increase of its relative concentration as other lipid species composing LDL, such as lysophospholipids, were reduced [57]. The authors of this study hypothesized that ceramides might be responsible for residual cardiovascular risk on statin therapy [57].…”
Section: Ceramides In Cardiometabolic Health and Diseasesmentioning
confidence: 67%